2014
DOI: 10.1787/9789264221444-en
|View full text |Cite
|
Sign up to set email alerts
|

The Adverse Outcome Pathway for Skin Sensitisation Initiated by Covalent Binding to Proteins

Abstract: Complete document available on OLIS in its original formatThis document and any map included herein are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area. No. 1, Guidance Document for the Development of OECD Guidelines for Testing of Chemicals (1993; reformatted 1995, revised 2006 No. 2, Detailed Review Paper on Biodegradability Testing (1995) No. 3, Guidance Document for Aquatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Individually, these cell lines are used to address key steps in the process of sensitization, namely activation of keratinocytes (key event 2) and activation and maturation of DCs (key event 3) of the skin sensitization adverse outcome pathway. 25 We found that exposure of the cocultured cells has the potential to increase their response to sensitizing chemicals, enabling the detection of prohaptens and supporting the identification of skin sensitization potency. 24,26,27 Additionally, 79.5% (31/39) concordance was found when potency was estimated on the basis of a prediction of four potency subcategories (extreme/strong, moderate, weak, and non-sensitizer) by linear interpolation of the lowest concentration needed to reach positivity for estimated markers (CD54 or CD86) as compared with LLNA EC3 values.…”
Section: Introductionmentioning
confidence: 61%
“…Individually, these cell lines are used to address key steps in the process of sensitization, namely activation of keratinocytes (key event 2) and activation and maturation of DCs (key event 3) of the skin sensitization adverse outcome pathway. 25 We found that exposure of the cocultured cells has the potential to increase their response to sensitizing chemicals, enabling the detection of prohaptens and supporting the identification of skin sensitization potency. 24,26,27 Additionally, 79.5% (31/39) concordance was found when potency was estimated on the basis of a prediction of four potency subcategories (extreme/strong, moderate, weak, and non-sensitizer) by linear interpolation of the lowest concentration needed to reach positivity for estimated markers (CD54 or CD86) as compared with LLNA EC3 values.…”
Section: Introductionmentioning
confidence: 61%
“…Chemical Name (Common Name) 1 3-methoxy-5-methyl-phenol 2 5-methyl-benzene-1,3-diol (orcinol) 3 2,5-dimethyl-benzene-1,3-diol (β-orcinol) SARs analysis indicated that compounds 1-8 belong to the resorcinol subgroup or are prone to be metabolized into a resorcinol structure with an additional aldehyde chemical function in compounds 4 and 5. As 1 could be metabolized into 2, and 7 and 8 are structural analogues of 6, compounds 2 to 6 were selected as potentially sensitizing molecules to be tested.…”
Section: Compoundmentioning
confidence: 99%
“…In order to assess the skin sensitization potential of chemicals, non-animal assays have been developed focusing on the first three main events of the adverse outcome pathway (AOP) defined for the sensitization phase: Protein binding, keratinocytes, and dendritic cells activation [1][2][3]. Among others, the direct peptide reactivity assay (DPRA) addressing protein binding, the KeratinoSens TM focusing on keratinocytes activation, and the human cell line activation test (h-CLAT) concentrating on dendritic cell activation, have been approved by the Organization for Economic Co-operation and Development (OECD) for testing health effects of chemicals [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After skin contact, substances causing allergic reactions, such as rash, are termed skin sensitizers, and the processes causing allergic reactions are termed skin sensitization (GHS 2017) [18]. The mechanisms of skin sensitization have been summarized in the form of an adverse outcome pathway (AOP) ranging from early events at the molecular level to adverse events through intermediate events, including the following four events (OECD 2014) [19]. The first event is the formation of covalent bonds between the electrophile; in other words, skin sensitizers covalently bind to the nucleophilic center of the proteins present in the skin.…”
Section: Introductionmentioning
confidence: 99%